Professionalization of Teaching in Nigeria - Ogieva, Adesuwa Evelyn; Izuhiuwa, Efosa-Ehioghiren Augustina (Journal of Education and Practice, 2024)
Purpose: The purpose of this study was to examine professionalization of teaching in Nigeria. Methodology: A descriptive survey approach and the population of the study consists of secondary school teachers in Edo State. One research question was formulated to guide the study while three hypotheses were formulated and tested at .05 alpha level. The sample of the study was 546 teachers (males 285 females 261). The method of collecting data was by the use of questionnaires. Data collected were analyzed with the use of descriptive statistics to answer the research question and inferential statistics t- test and analysis of variance to test the hypotheses. Results were presented in tables. Findings: The results showed that there is significant difference in the variables (gender, (X =35.13; SD=9.38) age, (F( 2,545) = 7.880P<.001) and academic status, (F(2,545) = 21.507;P < .001 ) in the study of professionalization of teaching in Nigeria. The findings indicated that professionalization of teaching in Nigeria is not a mirage but a reality, due to a lot of positive efforts the Teachers Registration Council of Nigeria (TRCN) had made towards teachers' registration, accreditation, certification, promotion, and development, discipline and making regulations to control the practices of teaching as a profession. Unique Contribution to theory, Policy and Practice: The study recommended among others that the Teachers' Registration Council Nigeria should stand up to their responsibility and continue to create the enabling environment and bring up innovative ideas to upgrade the quality of teachers in the teaching profession in Nigeria. Vibrant Orientation and enlightenment should be carried out at intervals nationwide by TRCN